2004
DOI: 10.1002/ajmg.a.30103
|View full text |Cite
|
Sign up to set email alerts
|

Severe lower limb defects in exstrophy of the cloaca

Abstract: We present here a patient with exstrophy of the cloaca associated with severe lower limb defects. The limb malformations include, on the right, a split foot with distal separation of the tibia and fibula, and on the left, attachment of the lower half of the left leg with a two-toed foot at nearly a right angle to the mid left thigh. A review of the literature indicates that 17-26% of patients with cloacal exstrophy also have lower limb defects. We hypothesize that cloacal exstrophy and associated lower limb de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Intriguingly, a recent study in the mouse has shown that a loss of Bmp7 combined with a half dose or complete loss of twisted gastrulation (Tsg) results in sirenomelia (Zakin et al, 2005). Bmp signaling defects in caudal mesoderm have been implicated by clinical researchers as one possible cause of analogous human malformations (Jain and Weaver, 2004). Zebrafish develop a ventral tail fin instead of a true set of hindlimbs, and loss of the ventral tail fin has been regarded as a readout for defects in ventral/caudal mesoderm (Tucker and Slack, 2004).…”
Section: Bmp Signaling and Human Developmental Defectsmentioning
confidence: 99%
“…Intriguingly, a recent study in the mouse has shown that a loss of Bmp7 combined with a half dose or complete loss of twisted gastrulation (Tsg) results in sirenomelia (Zakin et al, 2005). Bmp signaling defects in caudal mesoderm have been implicated by clinical researchers as one possible cause of analogous human malformations (Jain and Weaver, 2004). Zebrafish develop a ventral tail fin instead of a true set of hindlimbs, and loss of the ventral tail fin has been regarded as a readout for defects in ventral/caudal mesoderm (Tucker and Slack, 2004).…”
Section: Bmp Signaling and Human Developmental Defectsmentioning
confidence: 99%
“…Cloacal exstrophy with hindlimb defects may be related to abnormalities in the caudal mesoderm [32]. Because these defects often involve the more posterior parts of the body, some studies proposed that the cloacal defects induce several caudal defects including the most extreme form, namely caudal regression syndrome (CRS) [33].…”
Section: Introductionmentioning
confidence: 99%
“…A higher tendency towards side-to-side asymmetry is also observed [43]. A review of the literature by Jain and Weaver revealed an incidence of lower limb abnormality in 17e26% of patients with cloacal exstrophy [44]. Certain limb malformations like club foot and equinovarus deformities can be associated with myelomeningocele, which often accompanies cloacal exstrophy; however, a variety of true limb malformations including hypoplasia, absence, split foot and ectopic additional digits, have also been observed [44].…”
Section: Skeletalmentioning
confidence: 89%
“…A review of the literature by Jain and Weaver revealed an incidence of lower limb abnormality in 17e26% of patients with cloacal exstrophy [44]. Certain limb malformations like club foot and equinovarus deformities can be associated with myelomeningocele, which often accompanies cloacal exstrophy; however, a variety of true limb malformations including hypoplasia, absence, split foot and ectopic additional digits, have also been observed [44]. Given the mesodermal origin of internal limb structures, it is postulated that mesodermal deficiency in the caudal region of the developing embryo is the common underlying abnormality [44].…”
Section: Skeletalmentioning
confidence: 98%